Pengembangan Sumber Daya Aparatur Oleh Camat Dalam Perspektif Kepemimpinan Transformasional (Studi Pada Kantor Kecamatan Ngantang Kabupaten Malang ) - Roni Prasetyo (Jurnal Administrasi Publik, 2015)
Abstract: Apparatus Resource Development by sub-district in Transformational Leadership Perspective (Studies in Office Ngantang Malang ) . Both public and bureaucracy in the area to make the area into an autonomous region which refers to Law No. 32 of 2004 on Regional Government. Where the law is a step to organize households in a particular agency office Ngantang Malang to improve the quality of staff performance through the development of personnel resources. As in Office Ngantang, there are still many employees are still less professional in carrying out their respective duties, the district head in the perspective of transformational leadership to make efforts in developing personnel resources own sub-district has undertaken the development of personnel resources. Furthermore, looking at the indicators that can foster employee morale. As well as the factors that stimulate and inhibit the process of development of personnel resources. In this case in particular sub-district government district head in transformational leadership perspective optimally pursue the program with the objective of the program will have an impact to improve the professionalism of the performance of the employees. Keywords: Apparatus Resources Development , Leadership Trasnformational Â  Abstrak: Pengembangan Sumber Daya Aparatur oleh Camat dalam Perspektif Kepemimpinan Transformasional (Studi Pada Kantor Kecamatan Ngantang Kabupaten Malang). Mengacu pada Undang-Undang nomor 32 tahun 2004 tentang Pemerintahan Daerah. Dimana undang-undang tersebut merupakan langkah untuk menata rumah tangga pada suatu instansi khususnya kantor Kecamatan Ngantang Kabupaten Malang untuk meningkatkan kualitas kinerja para pegawai melalui pengembangan sumber daya aparatur. Seperti di Kantor Kecamatan Ngantang, masih banyak ditemui pegawai yang masih kurang profesional dalam melaksanakan tugasnya masing-masing, maka camat dalam perspektif kepemimpinan transformasional melakukan upaya-upaya dalam mengembangkan sumber daya aparatur. Camat Ngantang sendiri telah melaksanakan pengembangan sumberdaya aparatur yaitu melalui Pemberian motivasi, pendidikan dan pelatihan dan pengawasan.Selanjutnya melihat indikator-indikator yang mampu menumbuhkan semangat kerja pegawai. Serta melihat faktor-faktor yang mendorong dan menghambat dalam proses pengembangan sumber daya aparatur. Dalam hal ini pemerintah kecamatan khususnya camat dalam perspektif kepemimpinan transformasional mengupayakan program tersebut secara maksimal dengan tujuan nantinya program tersebut berdampak untuk meningkatkan profesionalitas kinerja para pegawai. Kata kunci: Pengembangan Sumber Daya Aparatur, Kepemimpinan Trasnformasional.Â Â